PRACTICALITY OF STEM INTEGRATED ELECTRONIC PHYSICS TEACHING MATERIALS ON ELASTICITY MATERIALS TO IMPROVE 21st CENTURY SKILLS OF STUDENTS - Vivi Mardian; Asrizal Asrizal; Akmam Akmam; Silvi Yulia Sari; Ida Nurshanty (PILLAR OF PHYSICS EDUCATION, 2022)
The breakneck internet access speed evidences the progress of society in the 21st century. Internet access speed is a form of community progress 5.0 in obtaining quality information. 21st-century skills have been born along with the development of information and communication technology (ICT). The rapid growth of ICT raises concerns about the human workforce that can be replaced by robots. The first actual condition is that 21st-century skills such as problem-solving, creative thinking, collaboration, and communication, are still low. The second exact condition is that the teaching materials used have not been integrated with STEM, with a value of 48%. The purpose of this study was to determine the practicality of developing STEM integrated electronics physics teaching materials to improve students' 21st-century skills. This study uses the type of research R&D (Research & Development). While the model used is the Plomp model. Based on the research results that have been done, it can be concluded that the results of the practicality of teaching materials in the one-to-one, small group, and field test trials are 80, 84, and 83, respectively. This can be interpreted that the electronic teaching materials developed are practical and can be used when learning physics.